EARLY PREVENTION OF CHRONIC DISEASES THROUGH HEALTH CHECKS AND HEALTHY HEART EXERCISES - Nanda Desreza; Ulfa Maulini; Marta Farwadi; Meutia Sukma A.S.; Cut Rara Hasviana; Yunia Dila Rosefa; Riska Rahmayana; Yuna Hazaini; Yusmanita Yusmanita; Elianur Juwita; Huriatul Huriatul; Mely Saputri (Transpublika Publisher, 2024)
Health is a crucial aspect that directly impacts human life, whether consciously or unconsciously. Those who are healthy are the ones who can truly enjoy life to the fullest. While hypertension is commonly associated with parents or the elderly, it can also affect adolescents and adults. This condition has become a significant issue not only in Aceh, Indonesia but globally. Hypertension serves as a risk factor for various other serious illnesses like heart disease, kidney failure, diabetes, and stroke. Engaging in cardiac exercises is highly beneficial for maintaining heart health. In Indonesia, these exercises have gained popularity, with several series designed to cater to individuals of all ages and fitness levels. This Community Service aims to detect and prevent chronic diseases, particularly hypertension, by conducting health assessments and raising awareness about the risks and management of hypertension. Based on the outcomes of Community Service activities in Gampong Bak Buloh, Kuta Baro District, Aceh Besar, it can be inferred that the community has gained awareness regarding the significance of health screenings to identify chronic diseases, particularly hypertension and its complications, thus enhancing the overall health status of the community.